2009
DOI: 10.1002/cyto.b.20501
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a dry format reagent alternative for CD4 T‐cell enumeration for the FACSCount system: A report on a Moroccan–Canadian study

Abstract: Background: Efforts to improve alternative CD4 T-cell counting methods are critical to accelerate the implementation of HIV antiretroviral therapy in resources limited regions. Substituting liquid format reagents to eliminate cold-chain transportation and refrigerated storage with dry format reagents contributes to higher efficiency supply management solution especially for laboratories at remote locations. ReaMetrix has developed dry format reagent kits compatible with the FACSCount system, a dedicated flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…At least one published performance evaluation study was found for each of the following technologies: BC Cytospheres [ 12 18 ], Dynal Dynabeads [ 14 , 18 22 ], Guava PCA [ 23 29 ], Partec CyFlow instruments [ 16 , 26 , 30 – 36 ], BD FACSCount [ 14 , 37 42 ]; BD Trucount tubes [ 43 46 ], BC Flow-Count fluorospheres [ 47 ], Cytognos Perfect-Count microspheres [ 48 ], SP Flow Cytometry using flow rate calibration [ 49 52 ]; BC PLG FlowCARE CD4 [ 53 ], Sysmex PocH-100i with Dynal Dynabeads [ 54 ], i+MED CD4 Select [ 55 ], Alere Pima Analyzer [ 56 58 , 61 ], PointCare NOW [ 60 ], Apogee Auto40 [ 59 , 63 , 64 ] and MBio Snap Count (MBio Diagnostics, Inc., Boulder, CO, USA [MBio]) [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…At least one published performance evaluation study was found for each of the following technologies: BC Cytospheres [ 12 18 ], Dynal Dynabeads [ 14 , 18 22 ], Guava PCA [ 23 29 ], Partec CyFlow instruments [ 16 , 26 , 30 – 36 ], BD FACSCount [ 14 , 37 42 ]; BD Trucount tubes [ 43 46 ], BC Flow-Count fluorospheres [ 47 ], Cytognos Perfect-Count microspheres [ 48 ], SP Flow Cytometry using flow rate calibration [ 49 52 ]; BC PLG FlowCARE CD4 [ 53 ], Sysmex PocH-100i with Dynal Dynabeads [ 54 ], i+MED CD4 Select [ 55 ], Alere Pima Analyzer [ 56 58 , 61 ], PointCare NOW [ 60 ], Apogee Auto40 [ 59 , 63 , 64 ] and MBio Snap Count (MBio Diagnostics, Inc., Boulder, CO, USA [MBio]) [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…The BD FACSCount system was used as reference system for CD4 T cell counting in the present evaluation. Indeed, the BD FACSCount is the oldest dedicated flow cytometer that has been extensively used since 1996 [32] and fully validated against reference flow cytometers in resource-limited settings [3235]. …”
Section: Discussionmentioning
confidence: 99%
“…Below, we describe a microfluidic‐based technique that uses a small quantity of analyte and is able to detect and distinguish weakly emitting particles. For the future, our approach is fully compatible with the use of dried reagents [e.g., ReaMetrix/BD (13)] to further simplify sample preparation.…”
mentioning
confidence: 99%